Application of the Eighth Edition American Joint Committee on Cancer Staging System for HPV‐Related Oropharyngeal Cancer Treated With Transoral Robotic Surgery. (9th October 2017) - Badhey, Arvind K.; Olson, Ashley; Kadakia, Sameep; Russo, Jack; Ting, Peter; Khalid, Mian; Yao, Mike; Teng, Marita S.; Genden, Eric M.; Miles, Brett A.; Chai, Raymond L.
Abstract : Objective: Analyze patients treated with transoral robotic surgery (TORS) in the context of the eighth edition of the American Joint Committee on Cancer (AJCC) staging system. Methods: Retrospective cohort study including 110 human papillomavirus‐related oropharyngeal cancer (HPV+OPC) patients with a minimum 1‐year follow‐up treated with TORS between 2007 to 2016. Kaplan‐Meier methods were used to estimate 3‐year disease‐free survival and assess differences in recurrence. Results: One hundred and ten patients with a median follow‐up of 54 months were analyzed. Of those, 85% of patients were male, with a median age of 60. Twenty‐two percent of patients received no adjuvant therapy; 43% received adjuvant radiation; and 35% underwent adjuvant chemoradiation. Extracapsular spread was identified in 24% of patients. Overall survival was 100%, with estimated 3‐year disease‐free survival (DFS) (95% confidence interval) of 87% (77, 93). Under the seventh edition of the AJCC, 5% of patients were stage I; 11% were stage II; 26% were stage III; and 57% were stage IVa. Twenty‐seven patients (25%) were upstaged on final pathology, whereas 15 patients (14%) were downstaged. Under the eighth edition of the AJCC, 94% of patients were stage I for both clinical and pathologic staging systems. Six patients (6%) were upstaged on final pathology, whereas six patients (6%) were downstaged. No factors demonstrated statistical significance for DFS. Within pathologic stage I, Kaplan‐Meier estimates for DFS did not reach statistical significance. Conclusion: The majority of patients undergoing TORS for HPV + OPC are stage I under the eighth edition of the AJCC staging system, with limited pathologic re‐staging compared with the prior system. Oncologic outcomes are favorable for this group. No clinicopathologic features are significant for DFS within pathologic stage I. Level of Evidence: 2b. Laryngoscope, 128:1133–1139, 2018